Methodological principles of classification of types of economic diagnostics - O. A. TOLPEGINA (Стратегические решения и риск-менеджмент)
The purpose of the study is determined by the need for further development and improvement of methodology of economic diagnostics. The study of theoretical issues and practical implementation of diagnostic studies and crisis management showed that the methodological basis of economic diagnostics needs work and updating, can extend practical approaches to research. Research complement and deepen the complex scientific and theoretical developments in the methodology of economic substantiation of diagnosis. The author presents a methodological approach to the classification of types of diagnostic studies on various grounds. The main emphasis in the developed classification of types is made on a thorough and complete rationale for each attribute, put with the basis of the classification of economic diagnostics, and describe the direction of the diagnostic study.